The Relationship between Plasma Levels of Large Neutral Amino Acids and Leptin in Women with or Without Obesity - Ming Der Chen; Yuh Min Song (Archives of Preventive Medicine - Peertechz Publications, 2016)
Obesity, characterized as excessive fat accumulation, is caused by interactions of genetic, environmental, and lifestyle factors [1]. Obesity increases the risk of various diseases including type 2 diabetes mellitus. Insulin resistance, commonly occurring in obese subjects, is attributed to the defects in insulin action on mediating the metabolism of macronutrients in target tissues [2]. Insulin increases amino acids uptake and protein biosynthesis in a tissue-specific manner [3]. In turn, certain amino acids can mediate insulin secretion [4]. Branched-chain (BCAA=valine+leucine+ isoleucine) and aromatic (AAA=tyrosine+phenylalanine+tryptophan) amino acids are of particular interest because they have distinctive effects to against obesity formation, as in regulating glucose oxidation [5] and satiety factors secretion [6,7]. Paradoxically, obese subjects have hyperaminoacidemia [8]. A close link between elevated plasma BCAA and obesity-related diabetes has also been found [9]. Elevated plasma BCAA may inhibit insulin signaling and contribute to insulin resistance [10]. Moreover, obese subjects have depressed activity in BCAA catabolism [11]. Leptin, produced by adipocytes, is secreted in proportion to the amount of body fat mass [12]. Besides regulating energy metabolism, leptin also positively affects amino acids uptake [13]. Since the changes in fasting plasma BCAA profile among ob/ob mouse (leptin deficiency), fa/fa rat (leptin receptor deficiency), and high-fat obese rodents (leptin resistance) are inconsistent [11,14,15], an interaction between leptin and amino acids in blood was thus proposed.